ANALISIS DAYA SAING BANDUNG SEBAGAI DESTINASI WISATA MELALUI MEMORABLE TOURIST EXPERIENCE (MTE) DAN CUSTOMER-BASED BRAND EQUITY FOR TOURIST DESTINATION (CBBETD) - Yuniawati, Yeni (2013)
Competition among tourism destinations has become increasingly severe. It is a challenge for all destination managers to continuously improve their competitiveness in the form of comparative and competitive advantage. In creating a competitive destination, there are two things that must be taken into consideration, that is tourists as the driving force and the destination marketing activities as the operating key driver. The paradigm shift from delivery focus to staged experience requires tourism destinations to be able to create memorable tourist experience for their visitors, while in terms of marketing, the ability to form a strong customer-based brand equity is one of the factors that determine the success of a destination in order to stay ahead in the competition. This study is aimed to analyze the influence of memorable tourist experience (MTE) and the customer-based brand equity for tourist destination (CBBETD) to Bandung's competitiveness as a tourism destination in the tourists' perspective. The method of this research is descriptive and explanatory survey with a sample size of 285 tourists from 9 destinations in Bandung. Data is collected by interviews, observations, questionnaires and the literature study and is analyzed using the Structural Equation Model (SEM) with LISREL program. The result shows that as a destination, Bandung is considered to be able to provide memorable tourist experience (MTE) for its visitors, but the brand equity is still low. The tourists' perception of Bandung's competitiveness as a tourism destination is somewhat high. On the other hand, the influence of memorable tourist experience (MTE) and the customer-based brand equity for tourist destination (CBBETD) on the competitiveness of Bandung is low. It is because competitiveness is a complex issue built on a variety of other variables that are more influential which are not examined in this study. Key words: customer-based brand equity for tourist destination, competitiveness, destination memorable tourist experience Persaingan antar destinasi pariwisata telah menjadi semakin ketat. Hal ini menjadi tantangan bagi semua pengelola destinasi untuk terus meningkatkan keunggulan mereka yang berupa comparative dan competitive advantage. Dalam menciptakan destinasi yang berdaya saing, ada dua hal yang harus diperhatikan yaitu wisatawan sebagai driving force dan kegiatan pemasaran destinasi tersebut sebagai operating key driver. Perubahan paradigma dari delivery focus menjadi staged experience menuntut destinasi untuk mampu menciptakan memorable tourist experience bagi wisatawannya, sementara dari sisi pemasaran kemampuan membentuk customer-based brand equity for tourist destination yang kuat merupakan salah satu faktor yang menentukan keberhasilan suatu destinasi untuk tetap unggul di tengah persaingan. Penelitian ini bertujuan untuk menganalisis pengaruh memorable tourist experience (MTE) dan customer-based brand equity for tourist destination (CBBETD) terhadap daya saing Bandung sebagai destinasi pariwisata dalam persespsi wisatawan. Metode penelitian yang digunakan adalah descriptive dan explanatory survey dengan ukuran sampel sebanyak 285 wisatawan nusantara dari 9 DTW yang tersebar di Bandung. Tehnik pengumpulan data yang digunakan adalah wawancara, observasi, angket serta studi literatur sementara tehnik analisis data yang digunakan adalah Structural Equation Model (SEM) melalui program LISREL. Hasil penelitian menunjukkan bahwa sebagai destinasi, Bandung dianggap memberikan memorable tourist experience (MTE) tinggi bagi wisatawannya, akan tetapi untuk ekuitas mereknya masih dianggap rendah. Daya saing Bandung sebagai destinasi beradasarkan persepsi wisatawan adalah cukup tinggi. Sementara pengaruh memorable tourist experience (MTE) dan customer-based brand equity for tourist destination (CBBETD) terhadap daya saing Bandung secara bersama-sama adalah rendah, hal tersebut karena daya saing adalah suatu hal yang kompleks yang terbangun atas berbagai variable lain yang lebih kuat pengaruhnya dan tidak diteliti dalam penelitian ini. Kata kunci: customer-based brand equity for tourist destination, daya saing, destinasi memorable tourist experience,